The relaxant effect of Tamsulosin in the vascular reactivity of goat isolated renal artery - Asaad, Aveen Muhsin; Salih Ibraheem Kakey, Ismail (Kurdistan Journal of Applied Research, 2019)
Alpha-blockers including tamsulosin, are medications that relax muscles in the urinary tract to facilitate stone passage into the bladder. This research aimed to investigate the possible action of tamsulosin (1 × 10-3 – 10-8 M), in the vascular reactivity of goat isolated renal artery by using the organ bath and PowerLab data acquisition system. The results of recording and analysing showed that tamsulosin caused a concentrated-dependent relaxation of endothelium intact renal artery rings precontracted with a high level of KCl (60 mM) or phenylephrine (PE) (10-5 M), also tamsulosin exhibited potent inhibitory effects on PE, and less potent on KCl-induced contractions. Renal artery rings preincubated with potassium (K+) channels blocker glibenclamide (GLIB), 4-aminopyridine (4-AP), prostaglandin I2 (PGI2) inhibitor (indomethacin) and epoxyeicosatrienoic acid (EET) inhibitor (Clotrimazole) have a significant effect in relaxation induced by tamsulosin. On the other side, subtype blockers from other K+ channels (tetraethylammonium, TEA), barium chloride (BaCl2) and inhibitor of nitric oxide (NO) synthase (L-Name) not exhibited any role in the relaxation effect of tamsulosin. Furthermore, the role of L-type of calcium channels (nifedipine) and tamsulosin, suggesting a Ca++ channel blocking mechanism has a relaxant effect in the urinary tract smooth muscles. Thus, from these results, it can be concluded that both potassium and calcium channels play an important role in relaxation effect of tamsulosin, which is mediated possibly through blocking of KV, KATP, PGI2, EET and voltage-dependent calcium channels.